Buddy and Earl Meet the Neighbors - Fergus, Maureen; Sookocheff, Carey 1972- (Toronto, 2018)
Buddy and Earl meet their new neighbors, Mister the bulldog and Snowflake the cat, while playing superheroes and when Snowflake gets in some trouble, Wonder Buddy and Super Earl come to the rescue.
Keywords: Dogs -- Juvenile fiction; Hedgehogs; Juvenile fiction; Neighbors; Juvenile fiction; Imagination -- Juvenile fiction; Picture books; Fiction